2021
DOI: 10.1108/ilt-02-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and tribological behavior of novel UHMWPE/vitamin-C/graphene nanoplatelets based hybrid composite for joint replacement

Abstract: Purpose This study aims to fabricate and investigate the tribological performance of ultra-high molecular weight polyethylene (UHMWPE)-based composite materials reinforced with 0.5, 1 and 2 weight percentage of graphene nanoplatelets (GNPs) while keeping the weight percentage of vitamin C constant at 2% for each composite. Design/methodology/approach In this paper, the composites were fabricated using hot pressing, and the dispersion of GNP/vitamin C/UHMWPE hybrid composite was investigated by X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Major reduction in the wear rate for the 2 wt% of GNP [27] GO agglomerates exhibited greater wear resistance in in pin-on-drum abrasive wear tests and lower COF in reciprocating ball-on-plate tests with stainless steel ball counterface. The authors attributed the superior tribological behavior of the nanocomposites to a superlubricity phenomenon of GO agglomerates resulting from the slip between their flakes, which are supposed to be agglomerated in an organized manner and promoted low friction.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Major reduction in the wear rate for the 2 wt% of GNP [27] GO agglomerates exhibited greater wear resistance in in pin-on-drum abrasive wear tests and lower COF in reciprocating ball-on-plate tests with stainless steel ball counterface. The authors attributed the superior tribological behavior of the nanocomposites to a superlubricity phenomenon of GO agglomerates resulting from the slip between their flakes, which are supposed to be agglomerated in an organized manner and promoted low friction.…”
Section: Introductionmentioning
confidence: 94%
“…[25] The removal of the oxygen groups makes the rGO predominately hydrophobic, which can be an important feature for some engineering applications. [20,21] Several studies [5][6][7]11,26,27] have shown that the low content of graphene nanofillers into the UHMWPE matrix can reduce the wear rate and COF of the tribosystems under sliding contact conditions. Table 1 summarizes recent literature results on the tribological behavior of UHMWPE/graphene-based nanocomposites during sliding wear tests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations